Implementation of Islamic Education Management at Islamic Boarding School: Implementasi Manajemen Pendidikan Islam di Pondok Pesantren - A. Nizar; Taufiq Churrahman (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the implementation of Islamic education management at Pondok Pesantren Qowiyyul Ulum Tahfiẕ Al-Qur'ȃn Surabaya. The study used qualitative research methods with a descriptive approach. The data collected were analyzed by content analysis, narrative analysis and discourse analysis. To describe the facts that occur in the field. Then the validity of the data is tested through the credibility test and transferability test. The results show that the implementation of Islamic education management at the Qowiyyul Ulum Tahfiẕ Al-Qur'ȃn Surabaya Islamic Boarding School has been running optimally and in accordance with the stages of management starting from planning by compiling programs according to needs. Organizing tailored to the duties and functions of each, and the implementation stage is carried out by all parties, as well as supervision carried out by the leadership of the Islamic boarding school. The obstacles in the implementation of Islamic education management are the lack of facilities and infrastructure, and the environmental conditions of the pesantren which are close to the localization area of ​​the Kremil so that the implementation of the pesantren program is not optimal. While the supporting factors come from the guardians of students, alumni, sympathizers, and the community.